If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ax + 6 = (x + 3) Reorder the terms: 6 + ax = (x + 3) Reorder the terms: 6 + ax = (3 + x) Remove parenthesis around (3 + x) 6 + ax = 3 + x Solving 6 + ax = 3 + x Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + ax = 3 + -6 + x Combine like terms: 6 + -6 = 0 0 + ax = 3 + -6 + x ax = 3 + -6 + x Combine like terms: 3 + -6 = -3 ax = -3 + x Divide each side by 'x'. a = -3x-1 + 1 Simplifying a = -3x-1 + 1 Reorder the terms: a = 1 + -3x-1
| 2w+2l=l | | -16x^2+8x+190=0 | | 1/4+w=61/3 | | -6(x+2)-11=21+4 | | -3(y+5)=15 | | 2overs-7=11 | | -9=-4(u-18)+-5 | | 6x3/6 | | 13+2p=-5-6p | | 0.09xX=110.30 | | X+(x-1)=2(x+3) | | 12x-2m= | | 3x4/9= | | -5x+2(4x-15)=-63 | | -3(-7w+4)-3w=4(w-5)-4 | | W=1000-0.2t | | 28a^3b^4+20a^2b^2-16ab^3= | | x^8=140 | | 40x-40=28 | | 67+4y-30=15y-12-4y | | 9+3y-3=7y+15-3y | | 8x+3y=67 | | 8x-5y=-9 | | 18+-9= | | V(w-l)=p | | 93-(7x+6)=7(x+6)+x | | 2x^2+14x+59=0 | | Ab+c=2 | | 0=p-20/-2 | | 8x+9y-(2x+y)= | | log(x)+8.75=0 | | -2(6x-7)+6x=5+2(2x-3) |